Circadian leptin concentration changes in critically ill heart failure patients - Cundrle, I; Suk, P; Sramek, V; Lacinova, Z; Haluzik, M (Physiological research, 2018)
Physiologically, leptin concentration is controlled by circadian rhythm. However, in critically ill patients, circadian rhythm is disrupted. Thus we hypothesized that circadian leptin concentration changes are not preserved in critically ill patients. Ten consecutive critically ill heart failure patients with the clinical indication for mechanical ventilation and sedation were included into our study. Plasma leptin concentration was measured every 4 h during the first day (0-24 h) and during the third day (48-72 h) after admission. During the first day, there were significant leptin concentration changes (ANOVA, p<0.05), characterized by an increase in concentration by 44 % (16-58 %); p=0.02 around noon (10 am-2 pm) and then a decrease in concentration by 7 % (1-27 %); p=0.04 in the morning (2 am-6 am). In contrast, there was no significant change in leptin concentration during the third day after admission (ANOVA, p=0.79). Based on our preliminary results, we concluded that in critically ill heart failure patients, the circadian rhythm of plasma leptin concentration seems to be preserved during the first but not during the third day after admission.
Keywords: Heart Failure; cirkadiánní rytmus; Leptin; Middle Aged; Critical Illness; lidé středního věku; lidé; srdeční selhání; senioři; leptin; mužské pohlaví; Female; Male; Circadian Rhythm; Aged; kritický stav; ženské pohlaví; Humans